Development of STEM-PjBL Learning Media to Improve Students' Critical Thinking Skills for Counting Whole Number and Fraction - Helen Novi Antika; Erina Ellen Rusmana; Annisa Salsabila; Ahmad Wachidul Kohar (Jurnal Inovasi Matematika, 2024)
This study aims to describe the process and results of the development of PjBL-based learning media integrated with STEM to improve students' critical thinking skills on the material of counting operations of whole numbers and fractions. This research is a development research with Plomp development model to develop learning tools in the form of Teaching Modules and Project Worksheets on arithmetic operations of whole numbers and fractions with STEM integrated project learning design. The instruments of this research are project worksheets, teaching modules, student response sheets, and pre-test and post-test sheets. Data collection techniques used questionnaires (validation sheets and student responses) and tests. Data analysis was conducted by testing the validity, practicality, and effectiveness of learning devices. The results showed that the learning devices obtained validity criteria of 87.9% for the Project Worksheet while 84.375% for the validity of the Teaching Module and each was classified as very valid. For the effectiveness criteria, the N-gain was 0.7512 in the limited trial and 0.7091 in the class trial and each obtained high effectiveness criteria. The learning tools obtained practical criteria for implementation with an average student response of 79.3% and 80.45% for project learning design. Thus, the learning tools are declared valid, effective, and practical to use.